FDM Based Custom 3D Printer Development in Robotic Arm Mechanical Prototype Printing. Issue 1 (1st December 2022) - Prianto, E; Herianto,; Herliansyah, M K; Pramono, H S; Husna, A F; Adam, R; Raditya, A E
Abstract: 3D printing is one of the most important tools of Industry 4.0. 3D printing technology has an advantage over traditional manufacturing processes, as it has the ability to convert 3D designs/models into ready-to-use products. The world of education needs to continue to adapt to technological developments. Making a mechanical prototype of a robotic arm is one of the main things to do to develop learning media in an educational environment. The mechanical prototype of the robotic arm can be made using 3D printing, so it will provide real implementation for education. The purpose of this study is to develop a custom 3D Printer learning media which is expected to facilitate the installation process and development of a mechanical prototype of a robotic arm as a form of implementation in the Mechatronics Engineering Education Study Program, FT UNY. This research was carried out based on the ADDIE model, namely Analysis, Design, Development, Implementation and Evaluation. The results of this study are a custom 3D printer based on FDM, both Cartesian and CoreXY types that can be used in learning in the Mechatronic Engineering Education Study Program. The test results show the average value of the measurement error of printing results is less than 2% so that it can be used in the learning process and supports the selected learning content. 3D printers can print robotic arm mechanical components with good results and low tolerances for printing precision.